Improving Student’s Adjective Vocabulary Through Animation Video on Fifth Grade - Jamil Arrohman; Teguh Satria Amin (Education & Learning, 2022)
The purpose of this study was to find out the application of animated videos can improve the adjectives of 5th grade students Mis integrated al-ikhwan tanjung morawa. This type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of three meetings. Furthermore, this research was carried out in four steps, namely planning, action, observation, and reflection. The object of this research is to improve students' adjectives. In collecting data, researchers used tests, observations and documentation. The results of this study indicate that the animation video media has a positive role in increasing the adjectives of the MIS Terpadu Al-Ikhwan Tanjung Morawa students. This can be proven by the average value of students from the initial value, cycle I, cycle II. The average value of the initial score was 57.2, in the first cycle it was 62.4, and in the second cycle it was 81.9.